Selexipag in Pulmonary Arterial Hypertension: Most Updated Evidence From Recent Preclinical and Clinical Studies. (21st December 2016) - Ghosh, Raktim K.; Ball, Somedeb; Das, Avash; Bandyopadhyay, Dhrubajyoti; Mondal, Samhati; Saha, Debjit; Gupta, Anjan
Abstract: Pulmonary arterial hypertension (PAH) is a relatively rare disease that, due to its chronic nature, has always been difficult to treat effectively. Selexipag is an oral prostacyclin (PGI2 ) agonist that was approved by US Food and Drug Administration (US FDA) in December 2015 for the treatment of PAH. After its success in phase 1 and phase 2 clinical trials regarding the convenient oral twice‐daily dosing and low side‐effect profile, selexipag raised the hope of controlling the disease progression in PAH patients. In the recently completed multicentered phase 3 study (GRIPHON), selexipag has been shown to reduce death and hospitalization due to PAH significantly, an effect that was consistent across different ranges of maintenance dose. In the same study selexipag use was also associated with an increase in 6‐minute walk distance (a measure of symptom severity) from baseline, but no significant improvement in all‐cause mortality could be observed. The results of the ongoing phase 3 studies (TRITON and TRANSIT‐1) are expected to throw some more light on the safety and efficacy of this novel molecule across various treatment scenarios. Hence, our article aims to summarize all the available information from preclinical and clinical studies published to date on the pharmacodynamics, pharmacokinetics, efficacy, safety (in general and in scenarios such as hepatic and renal function impairment), significant drug interactions (with warfarin and antiretroviral drugs), and clinical significance of oral selexipag in patients with PAH.